Plainwater : essays and poetry - Carson, Anne, 1950- (Vintage Contemporaries, 2000)
"Plainwater brings together five selections from Anne Carson's growing body of highly praised work." "Included are Mimnermos: The Brainsex Paintings, a present-day dialogue with a poet of the seventh century BC; Short Talks, one-minute lectures on topics as diverse as trout and Parmenides; Canicula di Anna, a chronicle of a phenomenology conference conducted in Perugia, Italy; The Life of Towns, verbal photographs that capture the essence of the nearly extinct "town"; and The Anthropology of Water, a travelogue of three moments in the journey of a woman's life."--Jacket.